The effect of motor perceptual games on aattention problem and spatial visual performance of educable mentally retarded girls - Salehian MH,; Sadeghi AS,; Hosseinzadeh PR, (Penerbit UKM, 2023)
The purpose of this study was to determine the effect of perceptual motor games on attention problems, ability and speed of cognitive processing and visual-spatial of educable mentally retarded girls. The study was a quasi-experiment. The research design included pre-test and post-test with control group with independent variable. The statistical population included educable mentally retarded girls. Thirty participants were randomly selected from the girls of exceptional schools in Tabriz and were randomly divided into experimental and control groups. The research measurement tool was the Connors Child and Adolescent Psychological Questionnaire. The reliability of the questionnaire was reported to be 0.79 by Cronbach’s alpha method.Reading performance test and spatio-visual performance test were performed for both groups as a pre-test. Perceptual motor game training sessions were performed in 16 sessions of 45 minutes for 8 weeks for the experimental group. Inferential statistics of covariance analysis were used for groups’ comparison using SPSS21 software at significant level of 0.05. The results showed that perceptual motor games had a significant positive effect in reducing the attention problems, improving the ability and speed of cognitive processing and improving visual-spatial performance in educable mental retarded girls.